Identification of Challenges Hindering Effective Stakeholder Management in Construction Projects - Emine Yüksel Deniz; Gulden Gumusburun Ayalp (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This study investigates challenges in the Turkish construction sector regarding stakeholder management. It aims to identify the key challenges that hinder effective stakeholder management, assess their frequency, and evaluate their significance. To achieve this aim, a systematic literature review (SLR) identified 69 potential barriers to effective stakeholder management in construction projects. A survey was developed based on the results of SLR and administered online and in person to various key stakeholders, including architects, civil engineers, material suppliers, and contractors. Data were collected from 164 project stakeholders across Turkey and analyzed using quantitative methods using SPSS 29.0. The study highlights the challenges impeding stakeholder management, providing insights into their frequency, impact, and importance rankings. By addressing these challenges, the research improves stakeholder management practices, ultimately fostering a more efficient and sustainable construction process.